2019
DOI: 10.1177/1090198119831755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between School Dropout and Pregnancy Among Adolescent Girls and Young Women in South Africa: A HPTN 068 Analysis

Abstract: Background. Prevention of both school dropout and teen pregnancy represent clear public health priorities for South Africa, yet their complex and potentially cyclical relationship has not been fully explored. Objective. To further understand how this relationship operates, we analyzed data from a randomized trial of young women aged 13 to 20 years enrolled in school in rural South Africa to estimate the association between pregnancy and subsequent dropout and between dropout and subsequent pregnancy. Method. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…In another study, adolescents who had ever been pregnant were more likely to report unprotected sex in the last 3 months when compared to nulliparous adolescents (39.8% vs. 30.5%). Furthermore, adolescents who had ever been pregnant were also more likely to report physical partner violence (47.2% vs. 16.8%) and transactional sex (21.9% vs. 16.9%) , known relational and structural risk factors for HIV infection . Research is needed to understand how the psychological, relational and structural changes that accompany the transition to adolescent motherhood influence unprotected sex.…”
mentioning
confidence: 99%
“…In another study, adolescents who had ever been pregnant were more likely to report unprotected sex in the last 3 months when compared to nulliparous adolescents (39.8% vs. 30.5%). Furthermore, adolescents who had ever been pregnant were also more likely to report physical partner violence (47.2% vs. 16.8%) and transactional sex (21.9% vs. 16.9%) , known relational and structural risk factors for HIV infection . Research is needed to understand how the psychological, relational and structural changes that accompany the transition to adolescent motherhood influence unprotected sex.…”
mentioning
confidence: 99%
“…The negative view is further amplified by the adolescents' expression of repercussions of adolescent pregnancy on school attendance as expressed in other studies. Moreover, related research has shown that keeping girl child in school is a way of averting adolescent pregnancy and motherhood [ 20 , 33 , 34 ]. The stigma starts form the girl herself to the school community.…”
Section: Discussionmentioning
confidence: 99%
“…It has further been urged that, once supported, these adolescent mothers can attain potential as much as their peers that postponed child bearing. Moreover debate has raged on that the undesirable lifestyles are not a consequence of adolescent pregnancies and motherhood but rather an extension of the predisposing factors [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy during adolescence is considered both an antecedent and consequence of school dropout in South Africa (SA). [1] Pregnancy during adolescence has implications that may result in detrimental health, educational, social and economic outcomes. [2] Many SA adolescents find themselves in an environment with a growing burden of HIV, where sexual and reproductive health needs are influenced by the numerous social determinants of health, such as poverty.…”
Section: In Practicementioning
confidence: 99%